2019
DOI: 10.1519/jsc.0000000000002052
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Muscle Activation Between Back Squats and Belt Squats

Abstract: A machine belt squat is a piece of equipment designed to allow the performance of squats while loading weight on the lifter's hips using a belt. The purpose of this investigation was to determine if belt squats differ from back squats in activation of the primary movers, and to determine the predictive capabilities of back squat load, training status, and anthropometric data on belt squat load. Thirty-one participants (16 males and 15 females) completed anthropometric measurements, a demographic questionnaire,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
7
1
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 19 publications
4
7
1
2
Order By: Relevance
“…Conversely, our findings of decreased GMax activity differed from previous work by Gulick et al (2015). The belt squat machine tested by Gulick et al (2015) operated by allowing the weight to slide along a fixed rod, whereas in this investigation and that by Evans et al (2017), where both observed decreased GMax activation, the load rotated about a pivot. Furthermore, previous literature has shown that when the resistance is along a fixed track, muscle activation is significantly less than a free weight back squat (Schwanbeck et al, 2009).…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…Conversely, our findings of decreased GMax activity differed from previous work by Gulick et al (2015). The belt squat machine tested by Gulick et al (2015) operated by allowing the weight to slide along a fixed rod, whereas in this investigation and that by Evans et al (2017), where both observed decreased GMax activation, the load rotated about a pivot. Furthermore, previous literature has shown that when the resistance is along a fixed track, muscle activation is significantly less than a free weight back squat (Schwanbeck et al, 2009).…”
Section: Discussioncontrasting
confidence: 99%
“…The results confirmed that utilizing a belt squat did not alter activation of the lower extremities except for a decrease in the GMax (35.2% impulse and 32.1% peak), GMed (54.1% impulse and 55.2% peak) and BF (12.2% peak). As a whole, our findings of decreased GMax activation (Evans et al, 2017) and no difference in quadriceps activation (Evans et al, 2017;Gulick et al, 2015) are consistent with previous research.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations